Common Fixed Point Theorems on S-Metric Spaces for Integral Type Contractions Involving Rational Terms and Application to Fractional Integral Equation - G. S. Saluja; Hemant Kumar Nashine; Reena Jain; Rabha W. Ibrahim; Hossam A. Nabwey (Journal of Function Spaces)
It has been shown that the findings of d-metric spaces may be deduced from S-metric spaces by considering dϖ,ϰ=Λϖ,ϖ,ϰ. In this study, no such concepts that translate to the outcomes of metric spaces are considered. We establish standard fixed point theorems for integral type contractions involving rational terms in the context of complete S-metric spaces and discuss their implications. We also provide examples to illustrate the work. This paper’s findings generalize and expand a number of previously published conclusions. In addition, the abstract conclusions are supported by an application of the Riemann-Liouville calculus to a fractional integral problem and a supportive numerical example.